Retrospective examination of complications observed in orthognathic surgical surgery in 85 patients - ATALI, ONUR (My University, 2022)
BACKGROUND: The aim of our study is to examine the possible complications, risk factors, and solutions encountered in orthognathic surgery in the light of the cases; we performed in our clinic. METHODS: This study includes a retrospective analysis of the records of 85 patients who underwent orthognathic surgery between 2015 and 2020 in Istanbul Pendik District Hospital Oral and Maxillofacial Surgery Service. The types of complications encountered during the operations were recorded in the study. Independent variables such as gender, age, number of operations, surgical site, and type of osteotomy were evaluated. Complications were evaluated according to the Clavien???Dindo classification. The data were presented for statistical analysis with a significance level of 0.05. RESULTS: Of the 85 patients included in the study, 40 were male and 45 were female. Of these patients, 65 had double chin operation and 20 had single chin operation. A total of 150 jaw osteotomies were performed, 78 of them in the maxilla and 72 in the mandible. While the maxilla was operated in 13 of the cases, in which single jaw operation was performed, only the mandible was treated in 7 of them. Complications were observed in 24 (10.57%) of a total of 227 osteotomies. Among the complications encountered, bleeding (8), nerve damage (7), malocclusion (3), infection (2), TMJ problems (2), bad split (1), and deviation at the tip of the nose (1) stand out, while complications were observed equally in men and women, complications were observed more frequently in cases with longer operative time (p<0.05). Complications were observed more frequently in bilateral sagittal split osteotomies (p<0.001) compared to Le Fort 1 osteotomies. Clavien???Dindo grade I complications were most common (72.04%) depending on the treatment. According to the Clavien???Dindo classification, there was no relationship between gender, age, duration of surgery, length of hospital stay, or surgical site, and the degree of complications (p???0.05). CONCLUSION: Post-operative malocclusion, bleeding, inferior alveolar nerve injury, infection, poor division, and infection are the most common complications in orthognathic surgery. It can be associated with factors such as the duration of the operation, the number of operations, the site of the operation, and the type of osteotomy which performed. It is thought that positive contributions can be made to the success of the surgery by considering these factors in the treatment planning, during the operation and in the post-operative follow-up part.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Acil Tıp; Medicine; Health Sciences; Surgery Medicine Sciences; Emergency Medicine; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Complication; orthognathic surgery; post-operation; RISK-FACTORS; STABILITY; Complication; orthognathic surgery; post-operation